KEEL BONE DAMAGE IN LAYING HENS – DIAGNOSTIC METHODS AND SEVERITY EVALUATION - S. Slavchev; L. Lazarov (Trakia Journal of Sciences)
Modern industrial egg production is accompanied by a number of clinical problems related to the welfare of laying hens. Sternum injuries are some of the most common pathologies in this animal species. The sternum in hens is 9-12 cm long and is located in the ventral sagittal plane (1). This is the largest bone in the body of the hen and serves as the basis of the entire skeleton. Bone growth and ossification is a process that begins in the cranial part and gradually ends in the caudal part. In the early stages of the egglaying period (between 28 and 40 weeks of age), it is not yet fully ossified, and the caudal tip often remains cartilaginous (1). This makes the sternum more vulnerable to damage than other long bones that complete their ossification in time (2). A large percentage of birds housed in aviary breeding systems are affected by sternal fractures. Due to the way chickens are raised, the sternum is affected by morphological changes that are important for animal welfare. The main concern stems from the pain experienced by laying hens with fractures and deformities of the sternum.